PENGARUH KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMODERASI - Setyaningsih, Riska Dewi; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
PROPER is a Corporate Performance Rating Assessment Program in Environmental Management. Thisprogram is one of the efforts which are done by Ministry of Environment to encourage the management of thecompany in managing the environment. This program is expected to able to encouragethe company in givingattention to the condition of the environment and to increase the performance of the management of theenvironment of the company. This research is meant to test the influence of environment performance to theperformance of the company by using csr as the moderating variable. The samplesare of 38 manufacturingcompanies which are listed in Indonesia Stock Exchange in 2013 and 2014 which have been selected by usingpurposive sampling. The data sources in this research has been retrieved from Indonesia Stock Exchange (IDX)and the result of PROPER measurement which has been published by the Ministry of Environment. In thisresearch, the hypothesis test appliesthe regressionequationlinear analysis technique with the instruments ofSPSS (Statistical Product and Service Solutions) application. The result of this research shows that theenvironment performance doesnât have any positive influence to the financial performance, PROPER whichinteracts with CSR doesnât have any positive influence to the financial performance.Keywords: Environment Performance, Financial Performance, Corporate Social Responsibility(CSR).